Novel two-dimensional Group-IV carbides containing C-2 dimers: Sizable direct band gap, high carrier mobility, and anisotropic properties for nanoelectronics - Kilic, Mehmet Emin; Lee, Kwang-Ryeol (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Exploring novel materials with superior properties is of a great significance for potential applications in future electronics and optoelectronics. Based on first-principles calculations, we predict new twodimensional (2D) group-IV carbides containing isolated C-2 dimers rather than individual carbon atoms, offering novel properties for nanoelectronics. The 2D carbides, namely th-XC2 (X = Si, Ge, Sn, and so on), are not only dynamically, mechanically, and thermally stable, but also exhibit exceptional properties such as anisotropic elasticity, ideal strength, and tunable phononic band gap. Moreover, they are all narrow direct band gap semiconductors with band gaps up to similar to 0.9 eV, which can be continuously tuned by strain and alloy engineering. They show excellent transport properties including strong anisotropic and small electron/hole effective mass and ultrahigh carrier mobilities (up to similar to 10(5)cm(2)V(-1)s(-1)). Excitingly, the anisotropy of the hole effective mass can be rotated by 90 degrees simply via alloying X element in tetrahexagonal carbon (th-C). Thus, the intrinsic carrier mobility in th-C is significantly enhanced by not only strain but also alloy engineering. In short, the 2D carbides are unique as composed of C-2 dimers with novel properties making them promising for nanoelectronics. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: MOLECULAR-DYNAMICS SIMULATIONS; ULTRASOFT PSEUDOPOTENTIALS; CARBON; TETRAHEXCARBON; NANOSTRUCTURES; SILIGRAPHENE; POINTS; GROWTH; STONE